Screening and Performance of Lactobacillus plantarum E11 with Bacteriocin‐Like Substance Secretion as Fermentation Starter of Sichuan Pickle. Issue 4 (30th September 2013) - Rao, Yu; Chang, Wei; Xiang, Wenliang; Li, Mingyuan; Che, Zhenming; Tang, Jie
Abstract Bacteriocinogenic Lactobacillus plantarum E11 was selected and applied for the controlled fermentation of Sichuan pickle. By agar well diffusion assay, Lb. plantarum E11 with bacteriocin‐like substances (BLISs) production against Escherichia coli, Listeria innocua and Staphylococcus aureus was selected from eight Sichuan pickle samples. Lb. plantarum E11 could grow in Chinese leaf mustard juice media and produce BLISs with favorable antibacterial characteristics. Novel starter consisting of Lb. plantarum E11 and Leuconostoc mesenteroides CICC (China Center of Industrial Culture Collection) 21859 were applied for controlled fermentation of Chinese leaf mustard, as well as commercial starter and spontaneous fermentation. The microbial dynamics in novel starter fermentation was similar as commercial starter fermentation and Lb. plantarum E11 comprised 35.3–63.8% of the total flora. The inhibition activity of novel starter fermentation against pathogens was achieved on the fifth day, which was faster and higher than commercial and spontaneous fermentation. Practical Applications The natural fermentation and nonsterile process make Sichuan pickle sensitive to foodborne pathogens. The innate immunity of Sichuan pickle conferred by natural lactic acid bacteria fermentation is not strong enough to suppress the foodborne pathogens especially at the early phase of fermentation. It is necessary to develop bacteriocinogenic starter culture with wide and stable antibacterial spectrum for Sichuan pickle fermentation. This study provided a novel starter including bacteriocinogenic Lb. plantarum E11, which could dominate the Sichuan pickle fermentation as traditional commercial starter and furthermore afford the Sichuan pickle self‐protection against foodborne pathogens at the early phase of fermentation.